2021
DOI: 10.1094/phyto-04-20-0147-r
|View full text |Cite
|
Sign up to set email alerts
|

Aggressiveness of Diverse French Aphanomyces euteiches Isolates on Pea Near Isogenic Lines Differing in Resistance Quantitative Trait Loci

Abstract: Aphanomyces root rot is a major disease in many pea-growing regions worldwide. The development of resistant varieties is necessary to manage the disease. Near isogenic lines (NILs) carrying resistance alleles at main validated quantitative trait loci (QTL) were developed by marker-assisted backcrossing (MAB). This study aimed to evaluate the aggressiveness of diverse French isolates of Aphanomyces euteiches on NILs carrying different resistance QTL. Fourty-three A. euteiches isolates from different French pea-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Quillévéré-Hamard et al [ 82 ] evaluated several NILs carrying QTL previously found [ 29 ] to contribute to resistance to ARR under both field and greenhouse conditions and reported a high potential for the use of these QTL in gene pyramiding and MAS breeding. In the current study, 344.1 K SNPs were identified to be polymorphic between the R and S bulks.…”
Section: Discussionmentioning
confidence: 99%
“…Quillévéré-Hamard et al [ 82 ] evaluated several NILs carrying QTL previously found [ 29 ] to contribute to resistance to ARR under both field and greenhouse conditions and reported a high potential for the use of these QTL in gene pyramiding and MAS breeding. In the current study, 344.1 K SNPs were identified to be polymorphic between the R and S bulks.…”
Section: Discussionmentioning
confidence: 99%
“…Pea NIL evaluations confirmed the significant effect of Aphanomyces resistance QTL combinations with the major QTL on chromosome 7 in decreasing disease severity and limiting yield reduction in highly infested fields. However, isolates were also identified in French pea fields, which were aggressive on these NILs (Quillévéré‐Hamard et al, 2018; Quillévéré‐Hamard et al, 2020), advocating the pyramiding of multiple resistance alleles for breeding varieties with high and durable levels of resistance (Pilet‐Nayel et al, 2017).…”
Section: Genetic and Genomic Determinants Of Resistance To Major Stresses In Pea And Faba Beanmentioning
confidence: 99%
“…LSMean values of root DS scores were used. More details are provided in Quillévéré-Hamard et al (2020).…”
Section: Matrix 20: Aphanomyces Euteiches-pisum Sativummentioning
confidence: 99%